Islam and CSR: A Study of the Compatibility Between the Tenets of Islam and the UN Global Compact - Williams, Geoffrey (Journal of business ethics, 2010)
This paper looks at whether the tenets of Islam are consistent with the ‘Ten Principles’ of responsible business outlined in the UN Global Compact. The paper concludes that with the possible exception of Islam’s focus on personal responsibility and the non-recognition of the corporation as a legal person, which could undermine the concept of corporate responsibility, there is no divergence between the tenets of the religion and the principles of the UN Global Compact. Indeed, Islam often goes further and has the advantage of clearer codification of ethical standards as well as a set of explicit enforcement mechanisms. Focusing on this convergence of values could be useful in the development of a new understanding of CSR in a global context and help avert the threatened “clash of civilisations”.